ChemInform Abstract: The Development of N‐Aryl Trifluoroacetimidate‐Based Benzyl and Allyl Protecting Group Reagents. Issue 16 (22nd April 2014) - Tsabedze, Sinele B.; Kabotso, Daniel E. K.; Pohl, Nicola L. B.
Abstract p‐Nitrophenyl substituted imidates (II) are efficient benzylating and allylating reagents in the presence of catalytic amounts of TmsOTf.